2021
DOI: 10.3389/fnins.2021.640016
|View full text |Cite
|
Sign up to set email alerts
|

Atrophy in the Left Amygdala Predicted Drug Responses in Idiopathic Generalized Epilepsy Patients With Tonic–Clonic Seizures

Abstract: We aimed to determine the alterations in the subcortical structures of patients with idiopathic generalized epilepsy with tonic–clonic seizures (IGE-GTCS) via MRI volumetry and vertex-based shape analysis and to evaluate the relationships between MRI measures and drug responses. In a follow-up sample of 48 patients with IGE-GTCS and 48 matched normal controls (NCs), high-resolution 3D T1WI was performed at baseline. After 1 year of follow-up, 31 patients were classified as seizure free (SF) and 17 as drug resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In contrast, McKavanagh et al 60 described bihemispheric structural and network alterations that differed between drug‐resistant and nonresistant patients. Li et al 61 also found differences between drug‐resistant and nonresistant patients, where atrophy of the basolateral region of the left amygdala was associated with drug resistance. In summary, no reproducible structural changes have yet been identified in drug‐resistant patients.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In contrast, McKavanagh et al 60 described bihemispheric structural and network alterations that differed between drug‐resistant and nonresistant patients. Li et al 61 also found differences between drug‐resistant and nonresistant patients, where atrophy of the basolateral region of the left amygdala was associated with drug resistance. In summary, no reproducible structural changes have yet been identified in drug‐resistant patients.…”
Section: Resultsmentioning
confidence: 96%
“…The network hypothesis is supported by evidence from fMRI, EEG, and (with limitations) neuropsychological studies that suggests altered functional connectivity in IGE patients compared to healthy controls, indicating that IGEs are network diseases 11 . Different resting state networks have been studied, and drug‐resistant patients seem to be more affected by alterations than drug responders 57,60,61 . This makes their brain more susceptible to seizures and explains the praxis induction and cognitive and psychiatric problems seen in IGE patients 54‐56 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Another study performed mice haploinsufficient in Brd2 , a gene associated with JME, and found decreased numbers of GABA neurons in the basolateral amygdala, which was consistent with the increase in aggressive behavior (Chachua et al., 2014). In addition, a previous study which investigated the alterations in the subcortical structures of patients with genetic generalized epilepsy, indicated the relationship between presence of focal atrophy in the basolateral amygdala and drug resistance (Li et al., 2021). Taken together, all of these findings suggested that the amygdala–hippocampus may play a key role in the pathogenesis of JME.…”
Section: Discussionmentioning
confidence: 99%
“…Subcortical nuclei are essential for multiple cognitive and motor functions, and thus are hypothesized to play a central role in the neural circuitry pathology underlying GGE [6][7][8] . Numerous volumetric structural studies have determined the volume alterations of subcortical nuclei in GGE, but the results have been inconsistent, with both atrophy and expansion reported in the thalamus [9][10][11][12] . Volumetric analysis methods do not capture the shape complexities of subcortical structures, and therefore, are not well-suited for characterizing detailed morphological abnormalities that may be present in GGE 13 .…”
Section: Introductionmentioning
confidence: 99%